Pengaruh Aplikasi Shopee terhadap Barang-Barang Lokal Menggunakan Karakter Cinta tanah Air pada Peserta Didik Kelas VI Sekolah Dasar - Junaidi, Junaidi; Fadillah, Putri (Cahaya Ilmu Cendekia Publisher, 2022)
Purpose of this Research: The purpose of this study was to determine the effect of using local goods on the character of the love of the students' homeland. Research Methods: The research method was conducted at SD Negeri 103/X Sidomukti in class VI. The data collection instruments used were questionnaires and multiple-choice questions. Data analysis used descriptive statistics and inferential statistics. Main Findings: The distribution of the two questionnaires revealed that the love for the homeland of students needed to be improved. Meanwhile, students' use of local goods is in a wrong category. The regression test results revealed that the use of local goods affected the character of the love for the homeland of students with a sig. 0.034. Novelty of this Research: The novelty in this study is found in a variable that is different from previous research, namely the character of love for the homeland. The limitation of this research lies in only the social media of the shopee application and the character of love for the homeland. The researcher recommends that there be more research to explore the influence of other social media. As well as more character values, especially in loving the homeland, that needs to be considered, such as tolerance, love for the homeland, peace, and others.